1997
DOI: 10.2527/1997.7582129x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of Aspergillus niger phytase in rendering phytate phosphorus available for absorption in pigs is influenced by pig physiological status.

Abstract: We performed an experiment with 112 piglets, 32 growing-finishing pigs, and 12 sows during pregnancy and lactation to test the hypotheses that apparent total tract digestibilities of P and Ca as well as the efficacy of Aspergillus niger phytase in rendering phytate P available in pigs depend on pig physiological status. All pigs were fed diets with identical feedstuff composition either without or with added microbial phytase (Natuphos, 500 FTU/kg diet). The diets contained 6.2 g Ca, 4.8 g total P, and 3.7 g p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
88
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 29 publications
8
88
3
Order By: Relevance
“…For [37]. This improvement could be related to a lower P need combined with better digestive utilization of phytic-P observed in finishing pigs [19,20,32,37]. In the present study the effects of the phytase preparation on phosphataemia of growing-fattening pigs were more pronounced during the first I9 days than later in the observation period.…”
Section: Introductionsupporting
confidence: 46%
“…For [37]. This improvement could be related to a lower P need combined with better digestive utilization of phytic-P observed in finishing pigs [19,20,32,37]. In the present study the effects of the phytase preparation on phosphataemia of growing-fattening pigs were more pronounced during the first I9 days than later in the observation period.…”
Section: Introductionsupporting
confidence: 46%
“…The results of experiments studying the effect of phytase on Ca digestibility in pigs are controversial. Some reports showed no effect (Yi et al, 1996;Harper et al, 1997;Sands et al, 2001) while others showed that phytase increased both ileal (Traylor et al, 2001) and total tract (Kemme et al, 1997) Ca digestibility. There are even studies demonstrating a greater effect of added phytase on Ca digestibility than on P digestibility (Johnston et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, lowering the pH of gastrointestinal digesta might increase the efficacy of supplemental phytase. Indeed, there are several experiments demonstrating a synergistic effect of diet acidification and phytase supplementation on P availability in pigs (Jongbloed et al, 1996;Kemme et al, 1997;Li et al, 1998) even though it is unclear whether this effect is due to the lower pH or the presence of the acid, mostly citric acid, itself (Han et al, 1998;Boling et al, 2000). Moreover, organic acids are metabolized in the body and intestinal digesta have a relatively strong buffering capacity, which suggests that a significant effect of diet acidification on the gastrointestinal tract pH can hardly be expected.…”
Section: Effect Of Microbial Phytase and Diet Fermentation On Ileal Amentioning
confidence: 99%
“…The results of some experiments have shown, however, analogically with trials on growing pigs, a beneficial effect of this enzyme on the digestibility of some nutrients and on the performance of these animals (Kemme et al, 1997;Jongbloed et al, 2004). It should be stressed that in almost all of the experiments on sows, the effect of phytase additive was examined when typical maize-soyabean meal diets, poor in intrinsic phytase, were fed (Hill et al, 2008).…”
Section: Introductionmentioning
confidence: 99%